Peran Perguruan Tinggi Negeri Berbadan Hukum (PTN-BH) terhadap Kinerja Kependidikan Islam - Riana Sari Sitorus; Ahmad Raihan; Ahmad Darlis; Indah Rizka Rahmi (Departement of Mathematics Education, 2023)
Education is very important in human life, because with education humans can develop and advance their potential to become human beings who have the ability to face various challenges in all areas of life, so to make this happen it is necessary to make improvements to the national education system. The term Legal Entity State University is first mentioned in Article 65 paragraph 1 of Law Number 12 of 2012, where it is stated that